(untitled) (The Journal of Geography Education in Africa, 2025)
Learners find it challenging to interpret topographic maps and orthophotographs. Although the chatbot Geography might be useful for this purpose, no research is available regarding its abilities and limitations. Thus, the aim of this multi-phase mixed methods research was threefold, namely (a) to explore Geography's topographic map and orthophotograph interpretation skills, (b) to determine the factors which can drive its adoption, and (c) suggest learning activities to promote responsible usage in geography classrooms. During the first phase, an explorative case revealed that Geography can be useful in interpreting topographic maps and orthophotographs but can also fabricate facts. During the second phase, the high adoption prediction score (six out of nine) indicated a need for responsible usage. Thus, learning activities were designed during the last phase to promote responsible use in geography classrooms. 1The title of this chatbot may cause confusion; thus, I have italicized to clearly distinguish between the chatbot, Geography, and the subject field, geography. Description provided in the paper.